Analysis of Mathematical Creative Thinking Process Based on Self-Confidence in Complex Number - Gunawan Gunawan; Kartono Kartono; Wardono Wardono; Iqbal Kharisudin (Universitas Negeri Semarang, 2022)
Abstract. This study aims to describe students' creative thinking process based on self-confidence. The research subjects were Mathematics Education students who took the Introduction to Complex Number. The topic of the material used is the complex number. This type of research is qualitative. Data collection techniques included creative thinking skills tests, self-confidence questionnaires, interviews, and documentation. A creative thinking skills test is made based on indicators of fluency, flexibility, originality, and elaboration. Based on the self-confidence questionnaire data, students were grouped into low, moderate, and high. From each category, two people were taken as informants. Data analysis uses the Miles and Huberman type: data reduction, data presentation, and conclusions. The mathematical creative thinking process consists of preparation, incubation, illumination, and verification stages. The results showed that students could fulfill cognitive activities during the preparation and verification stages. Each category has a different way and answers at the incubation and illumination stages. The thing that affects is the previous knowledge.